Diagnosis and fault tolerance of electrical machines, power electronics and drives - Cardoso, Antonio J. Marques (IET energy engineering series, 2018)
The book consists of six chapters and covers the following topics: an introduction to diagnosis and fault tolerance of electrical machines, power electronics and drives; voltage-source inverter-fed drives; switched reluctance machine drives; high-power synchronous machine drives; capacitors and DC-DC converters.